Left atrial diastasis strain slope is a marker of hemodynamic recovery in post-ST elevation myocardial infarction: the Laser Atherectomy for STemi, Pci Analysis with Scintigraphy Study (LAST-PASS) - Kato, Yoko; Lee, Wei Hao; Natsumeda, Makoto; Ambale-Venkatesh, Bharath; Takagi, Kensuke; Ikari, Yuji; Lima, Joao A. C. (Frontiers in Radiology, 2024)
Background: Left atrial (LA) mechanics are strongly coupled with left ventricular (LV) filling. The LA diastasis strain slope (LADSS), between the passive and active LA emptying phases, may be a key indicator of the LA-LV interplay during diastole. Aim: To investigate the LA-LV interdependencies in post-ST elevation myocardial infarction (STEMI), focusing on the LADSS. Materials and methods: Subjects with post-anterior STEMI who received primary percutaneous coronary intervention underwent contrast cardiac magnetic resonance imaging (MRIs) in acute (5 to 9 days post-STEMI) and chronic (at 6 months) phases. LADSS was grouped into 1, 2, and 3, representing positive, flat, and negative slopes, respectively. The cross-sectional correlates of LADSS Group 2 or 3 in comparison to Group 1 were identified, adjusting for demographics, LA indices, and with or without LV indices. The associations of acute phase LADSS with the recovery of LV ejection fraction (LVEF) and scar amount were investigated. Results: Sixty-six acute phase (86.4% male, 63.1±11.8 yrs) and 59 chronic phase cardiac MRIs were investigated. The distribution across LADSS Groups 1, 2, and 3 in the acute phase was 24.2, 28.9, and 47.0%, respectively; in the chronic phase, 33.9, 22.0, and 44.1%. LADSS Group 3 demonstrated a higher heart rate than Group 1 in the acute phase (61.9±8.7 vs. 73.5±11.9 bpm, p<0.01); lower LVEF (48.7±8.6 vs. 41.8±9.9 %, p=0.041) and weaker LA passive strain rate (SR) (-1.1±0.4 vs. -0.7 [-1.2 --0.6] sec-1 , p=0.037) in the chronic phase. Chronic phase Group 3 exhibited weaker LA passive SR (RRR = 8.8, p=0.012) than Group 1 after adjusting for demographics and LA indices; lower LVEF (RRR = 0.85, p<0.01), higher heart rate (RRR = 1.1, p=0.070), and less likely to be male (RRR = 0.08, p=0.058) after full adjustment. Acute phase LADSS Groups 2 and 3 predicted poor recovery of LVEF when adjusted for demographics and LA indices; LADSS Group 2 remained a predictor in the fully adjusted model (β=-5.8, p=0.013). Conclusion: LADSS is both a marker of current LV hemodynamics and its recovery in post-anterior STEMI. LADSS is an important index of LA-LV interdependency during diastole. Clinical trial registration: [https://clinicaltrials.gov/], identifier [NCT03950310].